Bitkilerde Programlı Hücre Ölümü - (:unkn) unknown (My University, 2018)
Programlı hücre ölümü (PHÖ) yaşlanmış, görevini yitirmiş, fazla üretilmiş, düzensiz gelişmiş veya genetik olarak hasarlı hücrelerin, organizma için güvenli bir şekilde yok edilmesini sağlayan, genetik olarak kontrol altında olan bir ölüm mekanizmasıdır. PHÖ vejetatif-generatif organ gelişimi sırasında ve biyotik-abiyotik stres şartları altında bitkilerin farklı organ ve dokularında görülür. Bitkilerde gelişim sırasında hücre ölümü; kök şapkası hücrelerinin değişimi, trakeal elementlerin oluşumu, su bitkilerinde havalandırma parankimasının oluşumu, trikom gelişimi, yaprak senesensi, eşey belirlenmesi ve üreme organlarının gelişimi sırasında ortaya çıkar. Bunun yanında virüs, bakteri, mantar gibi biyotik ve UV ışık, kuraklık, tuzluluk, sıcaklık, donma, sel, ağır metaller, pestisitler gibi birçok abiyotik stres faktörü bitkilerde PHÖ’ye yol açar. Bitkilerdeki PHÖ mekanizması hayvan hücrelerindekine benzer şekilde nukleus morfolojisindeki değişiklikler, kromatin yoğunlaşması, DNA fragmentasyonu, protoplastta büzülme, hücre iskeletinde değişikler ve kaspaz benzeri enzimatik aktiviteler ile gelişir. Apoptotik hücre ölümü görülmeyen bitkilerde, vakuoler ve nekrotik hücre ölümü olmak üzere iki tip ölüm vardır.

Cell death which is one of the basic characteristics of both prokaryotic and eukaryotic cells is encountered within the whole organism. Programmed cell death (PCD) is a genetically controlled mechanism, allows retired, dysfunctional, overproduced, irregularly developed or genetically damaged cells to be destroyed safely for organism. It has been first used in 1964 by Lockshin and Williams. Animal apoptosis which is best characterized form of PCD is used first in 1972 by Kerr et al. According to the recent biochemical and molecular studies PCD is categorized in three basic groups: apoptosis, autophagy and necrosis. Plants do not undergo apoptotic cell death, and cell death is classified into two groups as vacuolar and necrotic cell death. In vacuolar cell death, alterations in nucleus morphology, chromatin condensation, DNA fragmentation, protoplast condensation, vacuolization, generation of reactive oxygen species, alterations in the cytoskeleton and caspase like enzymatic activities are observed, as in animal cells. Necrotic cell death has different features from vacuolar cell death such as ATP depletion, cell and mitochondria swelling. PCD appears in different organs and tissues of plants during vegetative-generative organ development and under biotic-abiotic stress conditions. It occurs during the development of plants such as regeneration of root cap cells, formation of tracheal elements, formation of aerenchyma in hydrophytes, trichome development, leaf senescence, sex determination and male-female organ development. Biotic stress factors such as virus, bacteria, fungus and abiotic stress factors such as UV light, drought, salinity, temperature, freezing, flood, heavy metals, pesticides lead to PCD. Under biotic and abiotic stress factors, the balance between antioxidant enzymes and generation of reactive oxygen species (ROS) changes. ROS are free radicals and cause lipid peroxidation, protein oxidation, nucleic acid damage and enzyme inhibition. These alterations in the cellular structures lead to oxidative stress. ROS accumulation also causes caspase-like activities by activating vacuolar processing enzymes, metacaspases, saspases and phytaspases. These proteolytic enzymes execute cell death and cut their substrates from specific amino acid residues such as aspartic acid. PCD can be visualized by light, fluorescence and electron microscopy. Besides DNA fragmentation during cell death is determined by TUNEL, comet assay and gel electrophoresis. Moreover, cytoplasmic cytochrome c identification, caspase like activities and alterations of mitochondrial membrane potential can be identified by biochemical analyses. Although a lot of morphological characteristic features are identified, plant cell death is still not clear with regard to molecular aspects. Molecular characterization of PCD will lead in the future to a better understanding of the mechanisms of plant development and stress tolerance for developing high quality plants.
Programmed Cell Death in Plants
Keywords: Biyoloji